Over a million students use our free study notes to help them with their homework
2x2y + 2x + 4y - cos(πy) = 45Applying implicit differentiation:4xy + 2x2(dy/dx) + 2 + 4(dy/dx) + πsin(πy)(dy/dx) = 0Moving all (dy/dx) terms to one side:2x2 (dy/dx) + 4(dy...
We begin by rewriting it in a more workable form: 2x4 - 4x-1/2 + 3. Indices are easier to integrate than fractions.Now, we integrate each term separately. The first term is 2x4...
(x^2+4x+10)/(x+3)(x+4)(x+1) = A/(x+3) + B/(x+4) + C/(x+1) [A(x+4)(x+1) + B(x+3)(x+1) + C(x+3)(x+4)]/(x+3)(x+4)(x+1) = (x^2+4x+10)/(x+3)(x+4)(x+1) [A(x+4)(x+1) + B(x+3)(x+1) + C(x+3)(x+4)] = (x^2+4x+10) A(...
Differentiate the equationdy/dx=6x+2x(dy/dx)+2y-4y(dy/dx)Set this equal to zero and solve for dy/dx which gives:dy/dx=(2y+6x)/(4y-2x)For x=2 and y=4 dy/dx=5/3(y-yo)=m(x-xo)y-4=(5/3)(...
3x3 /3 + 4x6/(6x3) = x3 + 2x6/9 + c
←
201
202
203
204
205
→
Internet Safety
Payment Security
Cyber
Essentials